2008
DOI: 10.1007/s10695-008-9269-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of praziquantel applied per os on selected haematological and biochemical indices in common carp (Cyprinus carpio L.)

Abstract: The aim of the study was to assess the effects of the anthelminthic, praziquantel, on the haematological and biochemical indices of the blood of common carp (Cyprinus carpio L.). Fish were divided into six groups: two groups received 30 mg kg(-1) body weight (bw) of praziquantel, and two groups were given 50 mg kg(-1) bw of praziquantel mixed into the heat-treated amyloid vehicle. Fish in the remaining two groups were given only the amyloid vehicle and were used as controls. Fish were examined either 24 or 96 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 16 publications
(13 reference statements)
2
31
1
1
Order By: Relevance
“…Fish exposed to environmental pollutants exhibit a variety of physiological responses, including blood balance disturbances (Booth et al,1988). The evaluation of hematological characteristics in fish has become an important means of understanding normal and pathological processes and toxicological impacts (Sudova et al,2009). CuSO 4 at various concentrations exerted a certain influence on some of the blood indices studied.…”
Section: Introductionmentioning
confidence: 99%
“…Fish exposed to environmental pollutants exhibit a variety of physiological responses, including blood balance disturbances (Booth et al,1988). The evaluation of hematological characteristics in fish has become an important means of understanding normal and pathological processes and toxicological impacts (Sudova et al,2009). CuSO 4 at various concentrations exerted a certain influence on some of the blood indices studied.…”
Section: Introductionmentioning
confidence: 99%
“…Sudová et al (2009) found small, transient but significant decreases in HGB, PCV and RBC in carp fed a single dose of PZQ at 30 and 50 mg kg -1 BW. Their control carp, however, had HGB, PCV and RBC levels that were approximately half those of control YTK, pointing to substantial differences in haematological parameters between teleost taxa (Gascoyne and Hawkey 1992).…”
Section: Discussionmentioning
confidence: 79%
“…Immersion toxicity studies, however, do not inform oral toxicity because the mechanisms of uptake and toxicity differ. Sudová et al (2009) found that carp (Cyprinus carpio L.) fed 30 or 50 mg kg -1 PZQ in a heat-treated amyloid carrier displayed significantly decreased erythrocyte count, haemoglobin level, packed cell volume and total protein 24 h after delivery, but that these differences resolved by 96 h post-treatment. Sudová et al (2009) concluded that the detrimental effects of oral PZQ were small, and presumed that they were reversible.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The assessment of haematological parameters in fish is important means of understanding the normal, pathological processes and toxicological consequences due to toxic substances (Svobodava, 2001;Sudova et al, 2009). Alterations in blood biochemical parameters serve as an important diagnostic tool that can also be used for the detection of abnormalities in liver and other tissues (Banaee et al, 2011).…”
Section: Haematological Responsesmentioning
confidence: 99%